2022
DOI: 10.1038/s41598-022-08370-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of topological Dirac semimetal in Ca-based Zintl layered compounds CaM2X2 (M = Zn or Cd; X = N, P, As, Sb, or Bi)

Abstract: Topological Dirac materials are attracting a lot of attention because they offer exotic physical phenomena. An exhaustive search coupled with first-principles calculations was implemented to investigate 10 Zintl compounds with a chemical formula of CaM2X2 (M = Zn or Cd, X = N, P, As, Sb, or Bi) under three crystal structures: CaAl2Si2-, ThCr2Si2-, and BaCu2S2-type crystal phases. All of the materials were found to energetically prefer the CaAl2Si2-type structure based on total ground state energy calculations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…24,25 It proposes that the Zintl CaAl 2 Si 2 type material CaM 2 Bi 2 (M = Zn or Cd) is a topological insulator. 26 The AM 2 X 2 (A = Ca, Sr, or Ba; M = Zn or Cd; X = Sb or Bi) series of materials were confirmed as topological insulators with band inversion and the coexistence of insulating topological state and the Rashba effect in the BaCd 2 SbBi film was achieved. 27 Inspired by SrX 2 As 2 (X = Cd, Sn) non-magnetic materials, we propose the new idea that AEIn 2 As 2 (AE = Ca, Sr, Ba) topological insulators may also undergo topological quantum phase transitions or metal–insulator phase transitions.…”
Section: Introductionmentioning
confidence: 96%
“…24,25 It proposes that the Zintl CaAl 2 Si 2 type material CaM 2 Bi 2 (M = Zn or Cd) is a topological insulator. 26 The AM 2 X 2 (A = Ca, Sr, or Ba; M = Zn or Cd; X = Sb or Bi) series of materials were confirmed as topological insulators with band inversion and the coexistence of insulating topological state and the Rashba effect in the BaCd 2 SbBi film was achieved. 27 Inspired by SrX 2 As 2 (X = Cd, Sn) non-magnetic materials, we propose the new idea that AEIn 2 As 2 (AE = Ca, Sr, Ba) topological insulators may also undergo topological quantum phase transitions or metal–insulator phase transitions.…”
Section: Introductionmentioning
confidence: 96%
“…In the past decades, with the development of theoretical simulation and synthesis methods, some 2D materials have been successfully studied both theoretically and experimentally . These materials are black phosphorus, transition-metal dichalcogenides (TMDs), Janus TMDs, group IVA–VA compounds, MXenes, , and Zintl compounds. These 2D materials exhibit various outstanding properties. Thus, they have been successfully used in electronic, optoelectronic, and TE applications. , Also, these materials can be experimentally synthesized using various growth methods, such as epitaxial growth, chemical vapor deposition, mechanical exfoliation, and micromechanical cleavage .…”
Section: Introductionmentioning
confidence: 99%
“…Several comprehensive technical reviews on TIs have been conducted. Moreover, numerous theoretical studies have demonstrated promising results, which include materials exhibiting honeycomb-like phases such as III–V buckled honeycombs, bismuthene, and graphene, , MXenes, transition metal dichalcogenides (TMDs), organometallic frameworks, Janus materials, , ternary transition metal chalcogenides (TTMCs), , composite quantum compounds, and single-quintuple-layer Zintl compounds. , Furthermore, materials that exhibit nontrivial phases as a product of functionalization , or substrates effects have also been theoretically predicted, but are still in need of experimental investigation. Recently, a study in Zintl materials shows the tunability of topological states driven by alloying with highly magnetic atoms and a magnetic-field-driven changeover from a trivial insulator to a topological material with an applied magnetic field .…”
Section: Introductionmentioning
confidence: 99%